Transcriptomics and proteomics analyses of the PACAP38 influenced ischemic brain in permanent middle cerebral artery occlusion model mice - Hori, Motohide (BioMed Central, 2012)
INTRODUCTION: The neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) is considered to be a potential therapeutic agent for prevention of cerebral ischemia. Ischemia is a most common cause of death after heart attack and cancer causing major negative social and economic consequences. This study was designed to investigate the effect of PACAP38 injection intracerebroventrically in a mouse model of permanent middle cerebral artery occlusion (PMCAO) along with corresponding SHAM control that used 0.9% saline injection. METHODS: Ischemic and non-ischemic brain tissues were sampled at 6 and 24 hours post-treatment. Following behavioral analyses to confirm whether the ischemia has occurred, we investigated the genome-wide changes in gene and protein expression using DNA microarray chip (4x44K, Agilent) and two-dimensional gel electrophoresis (2-DGE) coupled with matrix assisted laser desorption/ionization-time of flight-mass spectrometry (MALDI-TOF-MS), respectively. Western blotting and immunofluorescent staining were also used to further examine the identified protein factor. RESULTS: Our results revealed numerous changes in the transcriptome of ischemic hemisphere (ipsilateral) treated with PACAP38 compared to the saline-injected SHAM control hemisphere (contralateral). Previously known (such as the interleukin family) and novel (Gabra6, Crtam) genes were identified under PACAP influence. In parallel, 2-DGE analysis revealed a highly expressed protein spot in the ischemic hemisphere that was identified as dihydropyrimidinase-related protein 2 (DPYL2). The DPYL2, also known as Crmp2, is a marker for the axonal growth and nerve development. Interestingly, PACAP treatment slightly increased its abundance (by 2-DGE and immunostaining) at 6 h but not at 24 h in the ischemic hemisphere, suggesting PACAP activates neuronal defense mechanism early on. CONCLUSIONS: This study provides a detailed inventory of PACAP influenced gene expressions and protein targets in mice ischemic brain, and suggests new targets for thereaupetic interventions.